Carcinoma of the appendix – A diagnostic challenge - Bhattarai, S; Yadav, BK; Kafle, P; Maharjan, N; Shrestha, SJ; Belbase, N; Kumar, S; Patowary, BN (Journal of College of Medical Sciences-Nepal, 2015)
INTRODUCTION Primary tumors of the appendix are rare. They are usually diagnosed after pathologic inspection of the appendix removed for suspected appendicitis. The main presentation is that of an acute appendicitis or as a palpable mass, mainly in the right lower quadrant. It mimics ovarian pathology in female because of close proximity to its anatomical structures. CASE PRESENTATION We report a case of 52 years female who presented to us in casualty with complains of pain abdomen and other findings suggestive of acute appendicitis. In spite of extensive preoperative investigations, the diagnosis was confirmed only after opening the abdomen as giant mucocele of appendix demanding right hemicolectomy as a treatment modality. CONCLUSION Although primary tumors of appendix is rare identity in the arena of surgery, it should be in the corner of thought as a possible diagnosis which require extensive surgery when compared to simple Appendicectomy. DOI: http://dx.doi.org/10.3126/jcmsn.v10i2.12953 Journal of College of Medical Sciences-Nepal, 2014, Vol.10(2); 36-40